Micro- and nano-pores in intrasalt, microbialite-dominated carbonate reservoirs, Ara Group, South-Oman salt basin. (June 2019) - Smodej, Jörg; Reuning, Lars; Becker, Stephan; Kukla, Peter A.
Abstract: Dolomitic microbialites form important exploration targets for the oil and gas industry in many parts of the world. It is known that a significant portion of their total porosity and potential storage capacity is formed by micropores. Despite their economic importance few studies attempted to characterize the micro-to nanoporosity in dolomitic microbialites. Recent advances in the field of microscopy now allow to image and analyze their pore systems on a hitherto unprecedented scale. This study evaluates pore systems in Neoproterozoic Ara-Group carbonates forming part of the deeply buried intra-salt A2C hydrocarbon play of the South-Oman Salt-Basin (SOSB). Micro- and nanoporosity there is hosted by aphanocrystalline and, to a minor extent, microcrystalline dolomite. Image analysis derived from broad-ion-beam milling and scanning-electron microscopy (BIB-SEM) of representative samples display a contribution between ∼50 and 100% from micro- and nanopores to total porosities which are up to ∼17%. The main diagenetic controls on microporosity in the A2C are the formation and preservation of primary or early diagenetic (aphanocrystalline) dolomite and the presence of evaporites, calcite and solid bitumen. Petrographic and petrophysical observations show good preservation of the original textural and geochemical attributes in most dolomite samples, even after burial to 5 km depth for the past 500 million years. This suggests a structurally and hydrodynamically isolated, rockbuffered system with a limited extent of cementation. Confocal laser-scanning microscopy (CLSM) reveals significant amounts of hydrocarbons which manifest as degenerated organic material in the carbonates. They originated from precursor bacterial organic matter in microbial laminite, thrombolite and peloidal source-rocks and might have prevented extensive recrystallization of the aphanocrystalline dolomite matrix and further cementation of the porespace. Primary dolomite might still be preserved in the A2C microbialites as petrographic observations reveal similarities in crystal sizes and the texture of euhedral aphanocrystalline dolomite as observed in comparable sedimentary systems. Highlights: Micro- and nanoporosity is hosted by microbial and grain-dominated carbonates. Dolomite crystal size controls distribution of micro- and nanoporosity. More than half of the total porosity (up to ∼17%) is micro- and nanoporosity. Good preservation of original textural and geochemical attributes in dolomite. Primary dolomite might still be preserved in the A2C microbialites.